Cassava stems and leaves as forage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Peruvian scientists are studying the possibility of using as forage parts of the cassava plant that are usually discarded when the roots are harvested. Faced with a food production imbalance as the population exceeds the capacity of the land to...